Peculiarities of structure and current of modern combat trauma among servicemen of the Armed Forces of Ukraine - I. M. Gaida; M. I. Badyuk; Yu. I. Sushko (Zaporozhye State Medical University, 2018)
The aim. To investigate the level and structure of combat trauma among servicemen of the Armed Forces of Ukraine in conditions of military operations. Materials and methods. The results of the analysis of the structure and character of the modern combat trauma in 954 soldiers - participants of the anti-terrorist operation, who were treated in the Military Medical Clinical Center of the Western Region (MMCC of the WR), are presented. Results It was found that the largest proportion among the injuries is injury of extremities - 52 % (496 wounded). In most of the wounded - 583 (61 %) - the state at the time of admission to the MMCC of the WR was rated as of mild severity. 94 wounded (10 %) received treatment in severe condition. In 277 wounded (29 %) state at the time of admission was assessed as of average severity. The longest treatment period was observed in patients with severe injuries - it was 36.6 days on the average. Duration of treatment in patients with injury of moderate severity was 21.8 days. In case of mild injury the duration of treatment for patients was 24.2 days. 6 (0.6 %) patients of the total number of treated patients (954 persons) died. These lethal consequences were caused by serious injuries: a mine-explosive injury of a severe degree (2 patients), a combined gunshot wound (3 patients), a gunshot wound of the head (1 patient). 604 patients (63.3 %) returned to military service without treatment without changing the category of suitability; 344 (36.1 %) patients are considered unsuitable for military service. Conclusions. Summarizing the results obtained, we can say that in the structure of wounds the greatest part was wound of extremities - 52 %. Among these the upper extremities were injured in 41.12 %, wounds of the lower extremities were 58.8 %. Modern combat trauma requires a long period of treatment and rehabilitation, which in the case of serious injuries is 36.6 days on the average. Treatment of modern combat trauma cannot be separated from rehabilitation measures. Therefore, treatment and rehabilitation of servicemen is a topical issue that today faces not only military but also civilian medicine and social protection services.